2022
DOI: 10.15421/022243
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cadmium salts on indicators of embryogenesis of rats

Abstract: Cadmium is a toxic heavy metal which is considered a dangerous environmental pollutant and has a detrimental effect on the organs of the reproductive system, the period of implantation and the development of embryos. The experiment presented in this article established the effect of cadmium salts (chloride and citrate) on the general progress of embryogenesis. For this purpose, 60 rats were randomly divided into three groups: control, experimental group with cadmium chloride exposure and experimental group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…At the same time, it was found that in the drinking water of the plain and foothill zone the level of cadmium exceeded the maximum permissible level. According to the literature (Bondareva et al, 2021;Kolosova et al, 2020;Mazur and Hutsol, 2022), the increase in cadmium levels may be due to the pollution of water bodies by industrial and domestic wastes with organic and mineral fertilizers, especially phosphate fertilizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it was found that in the drinking water of the plain and foothill zone the level of cadmium exceeded the maximum permissible level. According to the literature (Bondareva et al, 2021;Kolosova et al, 2020;Mazur and Hutsol, 2022), the increase in cadmium levels may be due to the pollution of water bodies by industrial and domestic wastes with organic and mineral fertilizers, especially phosphate fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they are part of salts, oxides and organometallic compounds, so this is what determines the danger of their release into the environment (Shevchuk et al, 2021). Phosphorus and complex fertilizers play a significant role in soil pollution (Bondareva et al, 2021;Kolosova et al, 2020). It is established that with excessive application of superphosphate to the soil, the content of cadmium in vegetable products increases by 4 times compared to the control (Ulianych et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even in low doses, cadmium has a toxic effect on the nervous system, immune system, reproductive system, and cardiovascular system [2,3]. Since cadmium is actively involved in physiological processes [4] and can cross the placental barrier, its accumulation leads to changes in the activity of various enzymes, shifts in the main morphological parameters, and significantly disrupts the balance of trace elements in the adult rat and embryos [5]. Cadmium can both increase the content of certain trace elements, causing their retention in tissues and organs and vice versa -cause significant losses of certain divalent cations, replacing them with itself.…”
Section: Connection Of the Publication With Planned Research Workmentioning
confidence: 99%
“…Навіть у низьких дозах кадмій має токсичний вплив на нервову систему, імунну систему, репродуктивну систему та серцево-судинну систему [2,3]. Оскільки кадмій активно залучається у фізіологічні процеси [4] і здатний долати плацентарний бар'єр, його накопичення призводить до зміни активності різних ферментів, зсуву основних морфологічних показників, а також суттєво порушує баланс мікроелементів дорослого організму щура та ембріонів [5]. Кадмій здатний як підвищувати вміст певних мікроелементів, обумовлюючи їх затримання у тканинах і органах, так і навпаки -викликати значні втрати певних двовалентних катіонів, замінюючи їх собою.…”
Section: зв'язок публікації з плановими науково-дослідними роботамиunclassified